2020
DOI: 10.33175/mtr.2021.241410
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cyber Ranges in the Maritime Context

Abstract: A good defensive strategy against evolving cyber threats and cybercrimes is to raise awareness and use that awareness to prepare technical mitigation and human defence strategies.  A prime way to do this is through training.  While there are already many sectors employing this strategy (e.g., space, smart buildings, business IT) maritime has yet to take advantage of the available cyber-range technology to assess cyber-risks and create appropriate training to meet those risks.   Cyber security training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Converselly, the seafarers' lack of competence and system awareness will present risk factors rather than risk reductions (Heering et al, 2020). The holistic framework to increase cybersecurity awareness and competence of seafarers includes theoretical education and practical training, and demonstrations and experiments, as well as assistance procedure development of identifying and dealing with cyber threats (Becmeur et al, 2017;Zăgan et al, 2018;Lovell and Heering, 2019;Tam et al, 2021b). The cross-sector capacities in the overlapping domains of automation, digital system, robotic, artificial intelligence, cyber, maritime shipping and navigation are the skills requirements for intelligent maritime shipping (Harris, 2021).…”
Section: Mitigating Maritime Cyber-riskmentioning
confidence: 99%
“…Converselly, the seafarers' lack of competence and system awareness will present risk factors rather than risk reductions (Heering et al, 2020). The holistic framework to increase cybersecurity awareness and competence of seafarers includes theoretical education and practical training, and demonstrations and experiments, as well as assistance procedure development of identifying and dealing with cyber threats (Becmeur et al, 2017;Zăgan et al, 2018;Lovell and Heering, 2019;Tam et al, 2021b). The cross-sector capacities in the overlapping domains of automation, digital system, robotic, artificial intelligence, cyber, maritime shipping and navigation are the skills requirements for intelligent maritime shipping (Harris, 2021).…”
Section: Mitigating Maritime Cyber-riskmentioning
confidence: 99%
“…A critical element in current simulation technologies, in maritime and aviation, is high-fidelity so trainers receive accurate mariner and pilot training (Liu et al 2020;Myers III, Starr, and Mullins 2018;Tam, Moara-Nkwe, and Jones 2020). Although costly, the benefits seem clear when preparing trainees for real environment, as highlighted in (Winn et al 2006) students learning oceanography using field experience, even with little prior understanding could learn quickly.…”
Section: The Reality Of Remote Controlmentioning
confidence: 99%
“…Understanding the security of a remote access environment from is critical for preventing both attacks and high-stress stress during an attack, whether or not it is successful. Maritime-cyber is a relatively new field and may need new facilities for researching (Tam and Jones 2019a) and training (Tam, Moara-Nkwe, and Jones 2020). Similar to the issue of training for an autonomous age, a survey in (Tam and Jones 2019c) found that 70% participants have not had any training cyber security, but 75% thought that addition cyber safety training would be useful for their tasks.…”
Section: Cyber Securitymentioning
confidence: 99%
“…The reliance on the Internet, operating with unprotected computers, and the fact that crews do not receive appropriate security training increase further the probability of a successful cyber breach. There is clear evidence that the absence of structured security awareness training for employees across the supply chain is a major source of vulnerabilities; as a result, hackers can use classical approaches such as spam emails or Denial-of-Service (DoS) attacks to achieve successful breaches [10,11]. A security plan providing recommendations to protect the maritime supply chain and a co-coordinated strategy with international marine organizations is a near-term necessity [12].…”
Section: Introductionmentioning
confidence: 99%